Upaya Meningkatkan Kemandirian Belajar Matematika Melalui Experience Language Pictorial Symbolic Applications (ELPSA) Pada Kelas VII C SMP Negeri 1 Ngablak - Himawan, Himawan (Faculty Of Education, 2022)
The aim of this study wanted to describe the level of independence in learning mathematics in VII C grade before the implementation of Experience Language Pictorial Symbolic Application (ELPSA) framework; to describe the implementation of Experience Language Pictorial Symbolic Application (ELPSA) framework to increase the independence of learning mathematics in VII C grade of SMP 1 Ngablak; and to describe the level of independence in learning mathematics in VII C grade after the implementation of Experience Language Pictorial Symbolic Application (ELPSA) framework. The design of the study is that the plot action research design: make an action plan, implementing the action, and reflection activities. The reflection is used as a guide for decision-making to continue or discontinue the study. Research conducted in the spiral cycles to the second cycle. Each cycle ends with an assessment test. The research data in the form of record of observations, field notes, documentation planning, and supervision results. The main data collection instrument was a researcher, while the supporting instruments is the observation, documentation. Data we analyzed by qualitative and quantitative techniques. Based on the research result, it can be concluded that the implementation of mathematics learning with the frame work of Experience Language Pictorial Symbolic Application (ELPSA) framework runs optimally in accordance with the standard (ideal) rules which include apperception, preliminary activities, core activities, and closing activities. The average magnitude of the increase in the independence of learning mathematics from the first cycle to the second is 10,89%. The average increase in the test from the first cycle to the second cycle is 3.31. Change in behavior that occur in students, among others, the number of children who bring learning tools increases and also increase their independence.